Comparing kinetic profiles between bifunctional and binary type of Zn(salen)-based catalysts for organic carbonate formation - Martín, Carmen; Kleij, Arjan W. (Beilstein Journal of Organic Chemistry, 2014)
Zn(salen) complexes have been employed as active catalysts for the formation of cyclic carbonates from epoxides and CO2. A series of kinetic experiments was carried out to obtain information about the mechanism for this process catalyzed by these complexes and in particular about the order-dependence in catalyst. A comparative analysis was done between the binary catalyst system Zn(salphen)/NBu4I and a bifunctional system Zn(salpyr)·MeI with a built-in nucleophile. The latter system demonstrates an apparent second-order dependence on the bifunctional catalyst concentration and thus follows a different, bimetallic mechanism as opposed to the binary catalyst that is connected with a first-order dependence on the catalyst concentration and a monometallic mechanism.
Keywords: CO2 chemistry; cyclic carbonates; kinetic studies; salen complexes; zinc